"Build Your Own House": Betty Spence's Design-Research in 1950s South Africa. Issue 3 (2nd September 2022) - Woudstra, Rixt; le Roux, Hannah
Abstract: This article examines the design-research of the white, South African, left-wing, liberal architect Elizabeth "Betty" Spence (1919–84) during early spatial apartheid. Building on Spence's fragmented archive of publications and interviews, we explore how she worked for and with disenfranchised Black township inhabitants on materializing alternative housing options. Spence's approach included careful observation of how different inhabitants—particularly women—used interior spaces. While her work responded pragmatically to distinct South African social, economic, and racial challenges, this article shows that her design-research was indebted to both European design thinking on the optimization of domestic space and American-South African debates on "race relations." Her concern with incremental housing, self-construction, and the process of building and homemaking in the townships, we argue, should be understood as a form of political action that enabled self-determination within the framework of modern urban life.